Optimization of Patrol Unit Turjawali Samapta in Preventing the Criminal Act of Breaking and Entering in the Jurisdiction of Klaten Polres - Putra, Mohammad Rizky Pratama (Advances in Police Science Research Journal, 2024)
The background of this research is related to the crime of theft with weighting in the jurisdiction of the Klaten Police in recent years being the highest compared to other crime cases. prevent criminal acts of theft by weighting in the jurisdiction of the Klaten Police?". This study used a qualitative approach with the type of field research by interviewing informants, observing, and studying documents. In addition, the data used is taken from several references such as articles, journal books, and online media news that are relevant to the problem variables discussed. This study uses management theory, SWOT analysis theory, and crime prevention theory that is related to existing problems, as well as several concepts that are relevant to the problem, namely the patrol concept and the optimization concept based on Perkabaharkam No. 1 of 2017 concerning Patrols. The Klaten Police Samapta Unit is the backbone in carrying out preventive police activities in preventing criminal acts of theft by weighting in the jurisdiction of the Klaten Police. In carrying out the patrol itself carried out by the Turjawali Unit Samapta Unit personnel, the Klaten Police still found several deficiencies in terms of planning, organizing, implementing and supervising and not in accordance with the Patrol SOP which has been regulated in Perkabaharkam No. 1 of 2017 concerning Patrols. In addition, there are factors that influence both internally and externally. On the other hand, to improve the implementation of patrols, it is necessary to have creative breakthroughs in efforts to increase the implementation of patrols.